Efficacy of manual removal and parenteral antibiotic therapy for retained foetal membranes in cattle - KULASEKAR, K; SARAVANAN, D; SENTHIL KUMAR, G; SRINIVASAN, R; SENRAYAN, M (The Indian Journal of Animal Reproduction, 2023)
Retained foetal membrane is an economically important post partum complication in dairy cattle. This study was undertaken to compare the efficacy between manual removal versus non-removal of retained foetal membranes, with parentral antibiotic therapy . Forty crossbred cows which retained the foetal membranes beyond 8 - 12 hours after normal calving, were randomly distributed into two groups. Group I cows were subjected to manual removal and parentral antibiotic therapy and Group II cows were subjected only to parentral antibiotic therapy. In both the groups the nature of lochia, uterine involution and milk yield were assessed once in 48 hours until recovery. There was no significant difference in the duration of uterine involution and milk yield between the groups. Parentral antibiotic therapy without manual removal can be suggested as a choice of therapy for retention of foetal membranes.